Bariatric surgery in severely obese adolescents: a single-centre experience. Issue 10 (30th June 2014) - Sachdev, Pooja; Makaya, Taffy; Marven, Sean S; Ackroyd, Roger; Wales, Jerry K; Wright, Neil P
Abstract : Background: Increasing numbers of severely obese young people undergo bariatric surgery in the USA with reports of substantial weight loss after 1 year. National Institute for Clinical Excellence 2006 suggests considering surgery for young people in 'exceptional circumstances'. We present six patients operated upon 2004–2012 at our centre in the UK. Case series: Six patients (4 male) aged 14–16 years (mean age 15.10) underwent surgery. Mean preoperative body mass index (BMI) was 62.7 kg/m 2 and BMI SDS +4.4. Comorbidities included hypertension, insulin resistance, obstructive sleep apnoea, limited mobility, benign intracranial hypertension and psychosocial issues. All six patients had prior involvement with local lifestyle weight management services and had pharmacological intervention. Four laparoscopic gastric bypass procedures, one laparoscopic gastric banding (patient had a gastric balloon prior to band) and one laparoscopic sleeve gastrectomy were performed. Results: There were no major postoperative procedural complications (one patient had a port rotation). Mean percentage of weight loss, as a percentage of total body weight at 6 and 12 months, was 22 and 27%, respectively. Average absolute weight loss at current follow-up is 54 kg. Mean BMI at 12 months postprocedure was 46.5 kg/m 2 —a mean fall of 16.2 kg/m 2 . Mean BMI SDS fell from +4.4 to +3.8 at 12 months and +3.1 at 2 years. Resolution of hypertension, improved school attendance and no progression to T2DM were the benefits noted. Conclusions: Recent systematic reviews and meta-analyses suggest that bariatric surgery results in sustained and clinically significant weight loss in paediatric populations. The surgical option should continue to be exercised with extreme caution only in severely obese adolescents and done so in appropriate case results in positive outcomes.